HONEYCOMBING AND DEFORMATION OF SIX WOOD SPECIES AND THEIR RELATIONSHIP WITH SEVERAL PHYSICAL - Karnita Yuniarti; Efrida Basri; Abdurachman Abdurachman (Jurnal Penelitian Hasil Hutan, 2017)
It is presumed that the wood susceptibility to drying defects is related to several physical properties. This paper examines the drying defects: honeycombing and deformation of six wood species (trema, fast growing teak, bayur, jabon, angsana and lamtoro) during high temperature drying and analyses their relationship with initial moisture content, T/R shrinkage ratio and density. Terazawa method was used to examine the defect during high temperature drying. Result shows that after high temperature drying, lamtoro suffers the worst honeycombing (level 4-6), and fast growing teak deforms severely (level 4-6). Regression analysis shows multiple regression models using all physical properties as predictors provides better estimation on deformation and honeycombing than single-predictor regression models. The multiple regression model for each defect could explain 57.52% and 39.46% of variation in deformation and honeycombing, respectively.